Pengaruh Kualitas Produk, Harga Dan Promosi Terhadap Keputusan Pembelian Sepatu Ventela (Studi Kasus Pada Mahasiswa FEB UNISMA Angkatan 2018) - Dicky Bagus Prastyo; N. Rachma; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The phenomenon in today's era makes it a challenge for business people. In running a business, business people need to continue to observe and track changing trends. This is because changes in trends that are always changing along with the times have a significant impact on the profits of consumer purchases. This has an influence on their behavior in choosing the shoes they will buy or which they consider the most appropriate and can actually meet their needs and desires. Quality shoes at competitive prices are the main way to win the marketing competition. In this case, Ventela shoes will apply the method by understanding the consumer decision-making process. Data analysis in this study consisted of instrument testing, classical assumption test, multiple linear regression analysis, hypothesis testing, and coefficient of determination test. The results of this study indicate that based on the results of the t-test there is a partial influence between product quality, price, and promotion variables on the decision to purchase Ventela shoes. The technique used in sampling is purposive sampling technique so that the data obtained by the researcher is directly by distributing questionnaires to respondents who have been determined with certain criteria, namely VENTELA Store consumers. The conclusion of this study aims to determine whether the variables of Product Quality, Price and Promotion affect the Decision to Purchase Ventela Shoes at the Sport Station Dinoyo Store. Keywords : Influence, Product Quality, Price, Promotion, Shoes.